Effect of Feeding Fry Red Tilapia with Spirulina on Fish Health - Eljaziri, Entisar Mohamed; Bin Omar, HishamAddin (The Libyan Journal of Science, 2021)
Feeding of Red Tilapia with commercial Spirulina microalgae experimental study (this volume) gave remarkable results. A complementary study investigating fish health was carried out. It showed that the best results were obtained for fish feed with 3% Spirulina in concordance with the experimental study in which the best return was achieved by this ration. Survival rate, reduction in mortality and protection from bacteria infection was ubiquitous with 3% ration showing maximum results.